Pulsed‐field ablation combined with ultrahigh‐density mapping in patients undergoing catheter ablation for atrial fibrillation: Practical and electrophysiological considerations. (9th January 2022) - Gunawardene, Melanie A.; Schaeffer, Benjamin N.; Jularic, Mario; Eickholt, Christian; Maurer, Tilman; Akbulak, Ruken Ö.; Flindt, Max; Anwar, Omar; Pape, Ulrich F.; Maasberg, Sebastian; Gessler, Nele; Hartmann, Jens; et al.
Abstract: Background: Pulsed‐field ablation (PFA) yields a novel ablation technology for atrial fibrillation (AF). PFA lesions promise to be highly durable, however clinical data on lesion characteristics are still limited. Objective: This study sought to investigate PFA lesion creation with ultrahigh‐density (UHDx) mapping. Methods: Consecutive AF patients underwent PFA‐based pulmonary vein isolation (PVI) using a multispline catheter (Farwave, Farapulse Inc.). Additional ablation, including left atrial posterior wall isolation (LAPWI) and mitral isthmus ablation (MI) were performed in a subset of persistent AF patients. The extent of PFA‐lesions and decrease of LA‐voltage were assessed with pre‐ and post PFA UHDx‐mapping (Orion™ catheter and Rhythmia™ 3D‐mapping system, Boston Scientific). Results: In 20 patients, acute PVI was achieved in 80/80 PVs, LAPW isolation in 9/9 patients, MI ablation in 2/2 (procedure time: 123 ± 21.6 min, fluoroscopy time: 19.2 ± 5.5 min). UHDx‐mapping subsequent to PVI revealed early PV‐reconnection in five case (5/80, 6.25%). Gaps were located at the anterior‐superior PV ostia and were successfully targeted with additional PFA. Repeat UHDx mapping after PFA revealed a significant decrease of voltage along the PV ostia (1.67 ± 1.36 mV vs. 0.053 ± 0.038 mV, p  < .0001) with almost no complex electrogram‐fractionation at the lesion border zones. PFA‐catheter visualization within the mapping system was feasible in 17/19 (84.9%) patients and adequate in 92.9% of ablation sites. Conclusion: For the first time illustrated by UHDx mapping, PFA creates wide antral circumferential lesions and homogenous LAPW isolation with depression of tissue voltage to a minimum. Although with a low incidence, early PV reconnection can still occur also in the setting of PFA.